Digitally Driven Aerosol Jet Printing to Enable Customisable Neuronal Guidance - Capel, Andrew J.; Smith, Matthew A. A.; Taccola, Silvia; Pardo-Figuerez, Maria; Rimington, Rowan P.; Lewis, Mark P.; Christie, Steven D. R.; Kay, Robert W.; Harris, Russell A. (Frontiers in Cell and Developmental Biology, 2021)
Digitally driven manufacturing technologies such as aerosol jet printing (AJP) can make a significant contribution to enabling new capabilities in the field of tissue engineering disease modelling and drug screening. AJP is an emerging non-contact and mask-less printing process which has distinct advantages over other patterning technologies as it offers versatile, high resolution, direct-write deposition of a variety of materials on planar and non-planar surfaces. This research demonstrates the ability of AJP to print digitally controlled patterns that influence neuronal guidance. These consist of patterned poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) tracks on both glass and poly(potassium 3-sulfopropyl methacrylate) (PKSPMA) coated glass surfaces, promoting selective adhesion of SH-SY5Y neuroblastoma cells. The cell attractive patterns had a maximum height ≥0.2µm, width and half height ≥15µm, Ra = 3.5nm, and RMS = 4.1. The developed biocompatible PEDOT:PSS ink was shown to promote adhesion, growth and differentiation of SH SY5Y neuronal cells. SH SY5Y cells cultured directly onto these features exhibited increased nuclei and neuronal alignment on both substrates. In addition, the cell adhesion to the substrate was selective when cultured onto the PKSPMA surfaces resulting in a highly organised neural pattern. This demonstrated the ability to rapidly and flexibly realise intricate and accurate cell patterns by a computer controlled process.